LEGAL REVIEW OF THE IMPLEMENTATION OF AGRICULTURAL LAND SHARECROPPING AGREEMENTS IN PIJORKOLING VILLAGE, DOLOK DISTRICT, NORTH PADANG LAWAS REGENCY - Nur Oloan; Sarmadan Pohan; Ridwan Rangkuti (Law Faculty of Universitas Bandar Lampung, 2025)
The purpose of this research is to understand the implementation of agricultural profit-sharing conducted by the customary law community in Pijorkoling Village, Dolok District, North Padang Lawas Regency, and to determine the compliance of agricultural land profit-sharing implementation with Law No. 2 of 1960. The research method used is a sociological juridical approach, with descriptive-analytical specifications, and purposive non-random sampling for sample determination. The analysis was conducted qualitatively to address the research problem. The research findings indicate that the implementation of the profit-sharing agreement for agricultural land in Pijorkoling Village, Dolok District, North Padang Lawas Regency does not use the profit-sharing agreement according to Law No. 2 of 1960 concerning profit-sharing agreements for agricultural land. Instead, they conduct profit-sharing agreements based on customary law that has been passed down through generations, which are agreements based on the approval and agreement between the landowner and the prospective cultivator, conducted verbally on the basis of trust. Regarding rights and obligations as well as the balance of profit-sharing, it is also based on the agreement of both parties. The profit-sharing ratio from the research is referred to as